1999
DOI: 10.1530/eje.0.1400420
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid concentrations of dimeric inhibins, activin A and follistatin in pregnancy

Abstract: Objective: The feto-placental unit is the major source of circulating concentrations of inhibin A and activin A in human pregnancy. The aim of this study was to measure the amniotic fluid concentrations of inhibin A, inhibin B, activin A and follistatin in pregnancies bearing male and female fetuses. Design and Method: Amniotic fluid samples collected by amniocentesis were stored at ¹20 ЊC. Dimeric inhibins, 'total' activin A and 'total' follistatin were measured using specific two-site enzyme immunoassays. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…18 Muttukrishana et al reported detectable levels of “total” activin-A from 15 to 20 weeks of gestation, but its concentration remained unchanged for the aforementioned GA interval. 25 A steady increase in the AF levels of inhibin-A from 15 to 18 weeks, was described by Wallace et al . 23,24 Petraglia and colleagues determined that between 23 to 40 weeks of gestation, activin-A was assayable in the AF of women with normal pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…18 Muttukrishana et al reported detectable levels of “total” activin-A from 15 to 20 weeks of gestation, but its concentration remained unchanged for the aforementioned GA interval. 25 A steady increase in the AF levels of inhibin-A from 15 to 18 weeks, was described by Wallace et al . 23,24 Petraglia and colleagues determined that between 23 to 40 weeks of gestation, activin-A was assayable in the AF of women with normal pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…15,22 However, most of our knowledge about human AF activin-A and inhibin-A is based on published reports which focused on their regulation in early pregnancy (8-20 weeks GA). 17,18,23,24,25,26,27 A common denominator for two of the referenced studies was that the levels of activin-A were higher in celomic fluid than in AF. 26,27 At 8-11 weeks, inhibin-A was undetectable in the AF.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of these acute changes in postnatal inhibin B concentration are unknown. Since we could not ®nd major changes in FSH levels, we speculate that in the postnatal period changes in paracrine growth factors, such as insulin and insulin-like growth factor-1, might potentiate FSH actions on granulosa cells and Sertoli cells inducing increased serum inhibin B concentrations in the 1st week of life [4,14,15,20]. The increase in inhibin B levels in neonates in the 1st week of life is in contrast with the changes in gonadal steroids: a brisk and short-lived increase in serum concentration of testosterone within hours of birth is seen in male neonates, while in both sexes the oestradiol concentration falls rapidly during the ®rst days of life [24,26].…”
Section: Discussionmentioning
confidence: 89%
“…The exact role of fetal inhibin B is unclear, but inhibins have been implicated in the regulation of steroid production in the fetal adrenal gland and gonads [25]. Although amniotic¯uid inhibin B concentrations have been shown to increase in the second trimester of pregnancy, it is not clear whether circulating concentrations of inhibin B are sucient to ful®l an endocrine role in suppression of FSH concentrations present in the third trimester [20]. We wondered whether measurement of serum inhibin B at the moment of neonatal screening on day 5 of life might give some information on gonadal development.…”
Section: Introductionmentioning
confidence: 99%
“…Although the levels of specific growth factors are not available for most commercially obtained serums, multiple studies have demonstrated that the concentration of activin A rises during pregnancy in maternal serum and is detectable at high levels in amniotic fluid and fetal serum [37][38][39][40][41][42][43]. In addition, studies have shown that deletion of INHBA in mice results in severe craniofacial abnormalities, including cleft palate and lack of lower incisors.…”
Section: Discussionmentioning
confidence: 99%